Can NBPT urease inhibitor in combination with Azospirillum brasilense inoculation improve wheat development? - Galindo, Fernando Shintate [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Buzetti, Salatiér [UNESP]; Pagliari, Paulo Humberto; Santini, José Mateus Kondo [UNESP] (Springer Nature, 2020)
This research was developed to investigate the use of Azospirillum brasilense to enhance N use in wheat cropping systems and to assess the potential interactions between inoculation and urease inhibitor N-(n-butyl)thiophosphoric triamide (NBPT). The study was set up under a no-till system in a Rhodic Hapludox. The experimental design was a randomized completely block design with four replicates arranged in a two N source (urea with and without NBPT) × five N rate applied as side dress (0–200 kg ha−1) × two inoculation (with and without A. brasilense) factorial scheme. Inoculation with A. brasilense in combination with application of 100 and 150 kg N ha−1 was found to increase grain yield by 19.6 and 18.8%, respectively. Inoculation also increased biomass N uptake by 66.9% when N was omitted. Inoculation and NBPT application were found to increase NUE by 23.7% compared to inoculation in combination with conventional urea and by 140% compared to NBPT without inoculation. In addition, inoculation increased plant height and NUE by 13.2 and 49%, respectively, compared with non-inoculated plots. Conventional urea and urea with NBPT had a similar effect on nutrient concentration, N uptake, leaf chlorophyll index, biomass weight and wheat grain yield. This study showed positive improvements in wheat production parameters as a result of inoculation, but the potential benefits of NBPT use were less evident. Further research should be conducted under growing conditions that provide increased N volatilization to better study the potential of NBPT application.
Keywords: N-(n-butyl)thiophosphoric triamide; Nitrogen fertilization; Nutrient leaf concentration; Plant growth promoting bacteria; Triticum aestivum L